Social Mobility in Europe 2004
DOI: 10.1093/0199258457.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Italian Mobility Regime: 1985–97

Abstract: Analyses changes in the Italian social mobility regime over the period 1985 to 1997. First, it is shown that both men’s and women’s absolute rates of mobility have remained substantially stable during the period under analysis. Some changes did occur in relative mobility changes: on the one hand, the strength of the barriers separating the urban manual and non-manual classes has increased somewhat; on the other hand, the degree of viscosity of agricultural classes has considerably decreased. Overall, these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…Because the ILFI is based on a complex sample design, the calculation of the uncertainty surrounding the estimates may be distorted. However, previous tests (Bernardi and Pisati 2002;Pisati and Schizzerotto 2004) have shown that the design effect tends to be fairly small (ranging in most cases from 0.8 to 1.2); therefore we decided not to incorporate sample design into the analysis (Table 1).…”
Section: Data Variables and Methodsmentioning
confidence: 99%
“…Because the ILFI is based on a complex sample design, the calculation of the uncertainty surrounding the estimates may be distorted. However, previous tests (Bernardi and Pisati 2002;Pisati and Schizzerotto 2004) have shown that the design effect tends to be fairly small (ranging in most cases from 0.8 to 1.2); therefore we decided not to incorporate sample design into the analysis (Table 1).…”
Section: Data Variables and Methodsmentioning
confidence: 99%
“…However, in France, Hungary, Poland and Sweden all change occurred between the 1970s and 1980s, and stability has prevailed since then (Breen and Luijkx 2004b:54). Changes in Ireland and Italy are quite minor (Layte and Whelan 2004;Pisati and Schizzerotto 2004), and only the Netherlands displays a sustained increase in mobility over the entire period considered (Ganzeboom and Luijkx 2004). Mobility has also been found to 426--AMERICAN S SOCIOLOGICAL R REVIEW increase over time in the United States between the early 1970s and the mid 1980s (Hout 1988).…”
Section: The Empirical Evidencementioning
confidence: 98%
“…While for the former the penalization is due to their higher probability of remaining in the agricultural class (results not shown), the limited probability of career mobility of the latter group is the consequence of the entrapment of late movers in the unskilled working class, as shown by previous analyses. The structure of career mobility in Italy is rigid, and blue‐collar workers, especially when unskilled, encounter strong barriers to their upward movement into any other classes (Panichella, ; Pisati & Schizzerotto, ). Hence, a late migration, which occurs after a period of inactivity in the South, produces disadvantages that also persist in the medium‐long run, making the process of integration difficult.…”
Section: Empirical Evidencementioning
confidence: 99%